Hyaluronan-mediated motility receptor antisense RNA 1 promotes hepatitis B virus-related hepatocellular carcinoma progression by regulating miR-627-3p/High Mobility Group AT-hook 2 axis. Issue 4 (1st April 2022) - Zhuang, Hai; Ma, Xiaoxia; Liu, Xiaoyan; Li, Chao; Li, Xinying; Wu, Ling; Wen, Maofei; Shi, Wenli; Yang, Xiaozhou
ABSTRACT: Hepatocellular carcinoma (HCC) is a common malignancy in the world, with high mortality and poor prognosis. Hepatitis B virus (HBV) is one of the key factors implicated in the occurrence of HCC. Increasing evidence suggests that miRNAs play important roles in the development and metastasis of HBV-associated HCC (HBV-HCC). Here, we performed CCK8 (Cell count kit-8), EdU (5-ethynyl-2'-deoxyuridine) incorporation assay, wound-healing assay, transwell assay to study the changes in the cellular phenotype. Luciferase reporter assay, RNA pull-down experiment, RT-qPCR and western blotting were employed to study molecular mechanism. In addition, we also constructed a mouse HCC xenograft model to verify the functional role of HMMR-AS1/miR-627-3p/HMGA2 signal axis in vivo . Our study demonstrated that HMMR-AS1 was highly expressed in HCC tissues and cell lines, suggesting its implication in the progression of HCC. In addition, in vitro experiments showed that high HMMR-AS1 expression facilitated the migration, invasion, and proliferation of HCC cells. We further revealed that HMMR-AS1 promoted the malignant phenotype of HCC cells by regulating miR-627-3p/HMGA2 axis. Together, our data suggest that HMMR-AS1 regulates HBV-HCC progression via miR-627-3p/HMGA2 axis. GRAPHICAL ABSTRACT: uf0001